The Relationship Of Information Sources And Level Of Anxiety Towards Participation In Iud Use In Mopah Baru Health Center Working Area Merauke, South Papua - Lusiani; Tri Hastuti; Hans Angelius Suharto; Erma Retnaningtyas (Universitas STRADA Indonesia, 2024)
One of the appropriate contraceptives to prevent pregnancy, especially in the long term, is the IUD. This study aims to determine the relationship between information sources and anxiety levels on participation in using IUDs in the Mopah Baru Community Health Center working area. This research uses a research design Analytical Observational with approach cross sectional. With technique simple random sampling there was sample of 87 respondents obtained, the independent variable (source of information and level of anxiety) and the dependent variable (participation in IUD use) used a questionnaire. Statistical tests are used Chi-Square to find out the relationship between the two variables. The results of research from 87 respondents showed that most of the criteria respondents did not get a source of information about IUD use as many as 54 respondents (62.1%), the majority of respondents experienced moderate anxiety about IUD use, namely 47 respondents (54%), and it was found that the majority of respondents The criteria for not participating in IUD use were 79 respondents (90.8%). Analysis uses statistical tests Chi-Square It was found that there was a relationship between the source of information and participation in using the IUD, namely p value = 0.000 < 0.05, and there was a relationship between the level of anxiety and participation in using the IUD, namely p value = 0.001 < 0.05. It is necessary to seek various sources of information from various parties (for example through print media, electronic media, through friends, family and competent health workers) before making a decision, especially information about the side effects and limitations of IUD contraception, so that respondents are not anxious and do not hesitate to take part in IUD use.